Legal Certainty in Judges’ Decisions Regarding the Authority of the Batam City Consumer Dispute Settlement Agency - Prastiyo, La Ode Agung; Nurlaily, Nurlaily; Sudirman, Lu (Jurnal Mediasas: Media Ilmu Syari’ah dan Ahwal Al-Syakhsiyyah, 2024)
This study examines issues related to the legal certainty analysis in judicial decisions regarding the authority of the Consumer Dispute Settlement Board (Badan Penyelesaian Sengketa Konsumen/BPSK) of Batam City, as observed in Batam District Court Decision Number 10/Pdt.Sus-BPSK/2021/PN Btm and Batam District Court Decision Number 25/Pdt.Sus-BPSK/2024/PN Btm. The core issue discussed in this research is the analysis of judicial considerations in ruling on matters related to the authority of BPSK Batam City and how these judicial decisions provide legal certainty in resolving disputes. The primary objective of this study is to analyze how judicial considerations influence legal certainty for parties involved in disputes concerning BPSK Batam City’s authority. This research is normative in nature, employing a literature study approach. The data utilized comprises secondary data, including various laws and regulations, books, theses, and relevant journal articles. Data collection methods involve a literature study, and the analysis is conducted using qualitative methods to interpret and summarize the research findings. The results indicate that the authority of BPSK Batam City in handling consumer disputes is limited in accordance with Law Number 8 of 1999 on Consumer Protection, which allows consumers to choose dispute resolution through BPSK or the court based on the consumer’s domicile. In the cases studied, BPSK Batam City frequently encounters challenges related to its competence in handling disputes that should be referred to the court, such as civil disputes or breaches of contract. [Penelitian ini mengkaji permasalahan terkait analisis kepastian hukum dalam putusan hakim mengenai kewenangan Badan Penyelesaian Sengketa Konsumen (BPSK) Kota Batam, seperti yang ditemukan dalam Putusan Pengadilan Negeri Batam Nomor 10/Pdt.Sus-BPSK/2021/PN Btm dan Putusan Pengadilan Negeri Batam Nomor 25/Pdt.Sus-BPSK/2024/PN Btm. Permasalahan yang dibahas dalam penelitian ini adalah menganalisis pertimbangan hakim dalam memutus perkara terkait kewenangan Badan Penyelesaian Sengketa Konsumen Kota Batam dan bagaimana putusan hakim memberikan kepastian hukum dalam menyelesaikan putusan sengketa, tujuan utama penelitian ini adalah untuk menganalisis bagaimana pertimbangan hakim mempengaruhi kepastian hukum bagi pihak yang bersengketa terkait kewenangan BPSK Kota Batam. Penelitian ini bersifat normatif dengan menggunakan pendekatan studi kepustakaan. Data yang digunakan adalah data sekunder yang terdiri dari berbagai peraturan perundang-undangan, buku, skripsi, dan artikel jurnal yang relevan. Metode pengumpulan data dilakukan melalui studi kepustakaan dan dianalisis menggunakan metode kualitatif untuk menginterpretasikan dan merangkum hasil penelitian. Hasil penelitian menunjukkan bahwa kewenangan BPSK Kota Batam dalam menangani sengketa konsumen terbatas sesuai dengan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen, yang memperbolehkan konsumen untuk memilih penyelesaian sengketa melalui BPSK atau pengadilan sesuai tempat kedudukan konsumen. Dalam kasus-kasus yang diteliti, BPSK Kota Batam sering kali menghadapi tantangan terkait kompetensinya dalam menangani sengketa yang seharusnya diserahkan kepada pengadilan, seperti sengketa keperdataan atau perbuatan wanprestasi].